Design and Application of Water Conservancy Model Management Service Platform - TIAN Maochun; ZOU Xianyong; YANG Yue; HE Qilian (Renmin Zhujiang)
The current water conservancy model cannot realize unified access and use,and the computing efficiency of multiple users,models,and schemes is low.In addition,the ability of sharing applications deeply bound with the system is weak.Therefore,the model fails to meet the requirements of intelligent water conservancy and digital twin watershed construction.In view of this,this paper designs a water conservancy model management service platform and applies it to practice.First,different types of water conservancy models are integrated,and their service interfaces are standardized,so as to uniformly receive model calculation service parameters and data in different formats and then convert them into required formats through platform adaptation,which avoids the problem of difficult unified invocation caused by differences in the interfaces of each model.Second,model computing resources are deployed and managed in a unified manner,and model calculation requests are distributed to different servers for calculation through task scheduling,so as to improve the resource utilization rate and reduce calculation time.Finally,a water conservancy model management service platform is developed,which integrates model management,model service,and model assembly functions,so as to provide the application system with model computing service.The application of multiple projects shows that the platform can integrate and share the resources of water conservancy models,give full play to the smart function,and provide support for the construction of intelligent water conservancy and digital twin watersheds.